Women's Murder Club : 7th Heaven - Patterson, James 1947-; Paetro, Maxine (New York : Little, Brown and Co., 2008)
Investigating the arson deaths of a wealthy couple, San Francisco detective Lindsay Boxer and Assistant DA Yuki Castellano find the case further complicated by the disappearance of a former governor's son, internal pressure, and the media.
Keywords: Fiction